Post-Traumatic Growth of Nurses Who Faced the COVID-19 Epidemic and Its Correlation With Professional Self-Identity and Social Support - Mo, Yuanyuan; Tao, Pinyue; Liu, Guiying; Chen, Lin; Li, Gaopeng; Lu, Shuyu; Zhang, Guining; Liang, Rong; Huang, Huiqiao (Frontiers in Psychiatry, 2022)
Abstract Objective: To investigate post-traumatic growth (PTG) and analyze its correlation with professional self-identity and social support in Chinese nurses who faced the coronavirus disease 2019 (COVID-19) epidemic. Methods: A cross-sectional descriptive design was used in this study. An online questionnaire was completed by 266 nurses who faced the COVID-19 emergency in Hubei Province, China. The Post-traumatic Growth Inventory (PTGI), Professional Self-identity Scale, and Perceived Social Support Scale were used to assess the level of PTG, professional self-identity, and social support. Descriptive, univariate analysis and multiple regression analyses were used in exploring related influencing factors. Results: Participants' mean scores were 96.26 (SD=21.57) for PTG, 115.30 (SD= 20.82) for professional self-identification, and 66.27 (SD=12.90) for social support. Multiple regression analysis showed that nurses from other provinces moving to support Hubei Province, professional self-identity, and social support were the main factors affecting nurse stress (P=0.014, <0.001, 0.017, respectively). Professional self-identity and social support were positively correlated with PTG (r=0.720, 0.620, respectively). Conclusions: There was phenomenon of PTG when the nurses faced COVID-19 in Hubei Province. Providing an active coping style helps to improve the level of PTG.